Penguatan Kapasitas Kelembagaan Pokdarwis sebagai Dasar Pengembangan Desa Eduwisata Pagelaran Berbasis (PRA) Partisipatory Rural Appraisal - Ken Sheyra Aiko Sha; Maulidyah Aulia Rahma; Zahwa Bintang Alfania; Olivia Ramadani (Medan Resource Center, 2025)
The proponent of Edu-tourism development is represented by the Pokdarwis (Tourismm Awareness Group). This also applies to the development of the Pagelaran Educational Tourism Village. The problems faced by Pokdarwis in Pagelaran Village include limited knowledge, coordination, and weak institutional structures. This empowerment offers the PRA approach as a model for strengthen Pokdarwis institutions. The implementation method uses several stages, namely problem identification, potential and objectives, solution planning, implementation, and evaluation. The application of PRA in this empowerment has resulted in successful active community involvement, structured management of the Pokdarwis institution, and the independence of Pokdarwis in managing Pagelaran Edu-tourism.